Inclusion and Exclusion Through Risk-based Justice: Analysing Combinations of Risk Assessment from Pretrial Detention to Release - van Eijk, Gwen (The British journal of criminology, 2020)
As the use of risk-based practices has proliferated in many jurisdictions, justice-involved individuals are often subjected to multiple risk assessments at various moments and with different purposes as they move through the criminal justice system. This article examines the ways in which different risk-based practices are combined and evaluates these combinations in terms of inclusion and exclusion of marginalized offender categories. By understanding risk-based practices in terms of the distribution of resources, the article conceptualizes how the accumulation of bias could exacerbate exclusionary effects and how contradictory risk-informed decisions could undermine inclusionary interventions. Understanding the interplay of different risk-based practices is essential for the practical and ethical judgement of risk-based justice.